Implementasi Model Group Investigation dalam Meningkatkan Motivasi dan Hasil Belajar PKn di MI Yappi Wiyoko - Rini Endang Lestari (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
This research aims to improve the motivation and learning outcomes of students in civil servant subjects. The subject of the study was grade II student MI Yappi Wiyoko Gunungkidul in the 2019/2020 school year. The results of the implementation of the group investigation model are obtained through observation sheets and questionnaires. The results showed that the average grade increase in students' motivation from cycle I was 74 to 83 in cycle II. While the initial test results compared to the final test results experienced a significant increase of 13% from the average initial test score of 69 to 82 after the action of cycle I and cycle II.